AGENT AND STRUCTURE RELATIONS IN THE COMMUNICATION PROCESS BASED ON HUMANIST AND RELIGIOUS VALUES AT THE PAMULANG UNIVERSITY IN SOUTH TANGERANG - Surti Wardani; Alo Liliweri; Ridzki Rinanto Sigit (International Journal of Social Science, 2024)
Pamulang University (Unpam), one of the private universities in the South Tangerang area, is established to meet the needs of the community by providing its own uniqueness and receiving very good interest. The uniqueness meant by that is the history of its founding to provide higher education for all people, especially for those people mentioned, the increase and large quantity of registered students, the availability of classes for students with disabilities, adequate lecture facilities, affordable tuition fees, and no building costs. One of the successes that has been achieved to date is the contribution of lecturers in implementing the tridharma of higher education. This is where the lecturer acts as an agent, actor, or agency, as known in Anthony Giddens' structuration theory. As a form of routine that produces social practice, the lecturer's tridharma must reflect humanist and religious values, including in the communication process within the university. These two values are in accordance with those stated in the university's vision, namely, "To become a university ranked in the top 40 at the national level based on humanist and religious values by 2025." This article analyzes the relationship between agents and structures in the communication process based on humanist and religious values at a private university in South Tangerang. The research used a qualitative method with a critical theory paradigm and an interpretive phenomenological approach. The results show that Unpam is able to manage and strive to pursue its vision through the tridharma of higher education, with the contribution of lecturers who act as agents, actors, and agencies. The routine activities of agents form a duality of structure and are related by mutual influence and reciprocity (interplay) that reflect most of the implementation of both humanist and religious values. Forms of communication that are full of humanist values, such as when lecturers greet each other, provide non-differentiating classroom learning, and interact with students and the community in PkM activities, including coordinating work on research activities, Meanwhile, religiousness can be seen in the form of greeting words and sentences, praying before and after activities, religious attributes worn as characteristics, tolerance during worship, the formation of the Institute for Religious Studies, and also religious studies. On the other hand, the role of agents still needs to be optimized as gatekeepers and/or opinion leaders because, as educators, they provide role models, especially for students (predominantly from the marginalized and lower middle class) and also the general public. Meanwhile, the university needs to have an organizational culture to strengthen motivation for academics, direction, and foundation in behavior and attitudes, which can be taken from humanist and religious values, as well as the motto Sharing for the Country, alongside the implementation of a code of ethics, to help realize its vision in 2025